ANALISIS HIDROLIKA PELIMPAH GOLENG DAN SWD 1 DALAM PENGENDALIAN DEBIT BANJIR SUNGAI WULAN - Alamsyah, Nurul Ikhsan; Wahyudi, Slamet Imam; Niam, Moh Faiqun (Universitas Islam Sultan Agung, 2025)
ABSTRACTFlood control in the coastal areas of Central Java, particularly along the SWD 1 Channel and the Goleng Spillway, faces significant hydraulic challenges due to sedimentation and land-use changes. This study aims to evaluate the hydraulic capacity of the Goleng Spillway and the SWD 1 Channel in reducing the Q25 flood discharge from the Wulan River, as well as to identify critical overflow points and effective mitigation scenarios. Hydraulic simulations were conducted using the HEC-RAS software under three scenarios: (1) inflow from the Goleng Spillway, (2) local flooding within the SWD 1 watershed, and (3) a combination of both. Input parameters included the Q25 design discharge, DEM-based topography, and cross-sectional channel geometry. The simulation results indicate that several cross-sections (from STA 0+025 to STA 31+000) are unable to accommodate the Q25 discharge effectively, with water surface elevations ranging from 1.18 to 7.9 meters. The most critical condition occurs along the left bank of SWD 1 due to the absence of embankment elevation. While the normalization design improved flow capacity, it was insufficient to manage the combined extreme inflows. Integrated structural interventions, such as elevating the left embankment and optimizing spillway geometry, are recommended to enhance flood resilience in the lower Wulan River region.Keywords: SWD 1, Goleng Spillway, flood, Q25, HEC-RAS, embankment, hydraulics. ABSTRAKPengendalian banjir di wilayah pesisir Jawa Tengah, khususnya di Sungai SWD 1 dan Pelimpah Goleng, menghadapi tantangan kapasitas hidrolika akibat sedimentasi dan perubahan tata guna lahan. Penelitian ini bertujuan untuk mengevaluasi kapasitas hidrolik Pelimpah Goleng dan Saluran SWD 1 dalam mereduksi debit banjir Q25 Sungai Wulan, serta mengidentifikasi titik-titik kritis luapan dan skenario mitigasi efektif. Simulasi hidrolika dilakukan menggunakan perangkat lunak HEC-RAS dengan tiga skenario: (1) inflow dari Pelimpah Goleng, (2) banjir lokal DAS SWD 1, dan (3) kombinasi keduanya. Parameter input meliputi debit desain Q25, topografi DEM, dan geometri penampang saluran. Hasil simulasi menunjukkan bahwa beberapa penampang (STA 0+025 hingga STA 31+000) tidak mampu menampung debit Q25 secara optimal, dengan muka air mencapai 1,18–7,9 m. Kondisi paling kritis terjadi pada sisi kiri SWD 1 akibat ketiadaan peninggian tanggul. Desain normalisasi terbukti meningkatkan kapasitas, tetapi tidak cukup mengatasi kombinasi inflow ekstrem. Intervensi struktural terintegrasi, seperti peninggian tanggul kiri dan optimalisasi geometri pelimpah, disarankan untuk memperkuat ketahanan banjir wilayah hilir Sungai Wulan.Kata Kunci: SWD 1, Pelimpah Goleng, banjir, Q25, HEC-RAS, tanggul, hidrolika.